Double phase-image encryption using gyrator transforms, and structured phase mask in the frequency plane. (April 2015) - Singh, Hukum; Yadav, A.K.; Vashisth, Sunanda; Singh, Kehar
Abstract: Fully-phase image encryption is considered more secure as compared to an amplitude image encryption. In the present paper, an encryption scheme is proposed for double phase-images. The phase-images are bonded with random phase masks and then gyrator transformed. The two resulting images are then added and subtracted to give intermediate images which are bonded with a structured phase mask (SPM) based on devil's vortex Fresnel lens (DVFL) in the frequency plane. Thereafter, the images are once again transformed using a gyrator transform (GT) to give the corresponding encrypted images. The use of a structured phase mask enhances the key space for encryption and also overcomes the problem of axis alignment associated with an optical set-up. The decryption process is the reverse of encryption. The validity of the proposed scheme is established from the computer simulation results using MATLAB 7.1 platform. The performance of the scheme is evaluated in terms of mean-squared-error (MSE) between the input-, and the decrypted images. In addition, the sensitivity to encryption keys such as SPM parameters, and transform angles of GT is investigated. The technique is likely to provide enhanced security in view of the increased number of encryption parameters. Robustness of the system against occlusion and noise attacks has also been investigated. Highlights: An encryption scheme is proposed for double phase-images in the gyrator domain. We have used a structured phase mask (SPM) based on devil's vortex Fresnel lens (DVFL) in the frequency plane. The validity of the proposed scheme is established from the computer simulation results using MATLAB 7.1 platform. The performance of the scheme is evaluated in terms of mean-squared-error (MSE) between the input-, and the decrypted images. The sensitivity to encryption keys such as SPM parameters, and transform angles of GT orders is investigated. Robustness of the system against occlusion and noise attacks has also been investigated.